Monitoring vegetation drought using MODIS remote sensing indices for natural forest and plantation areas - Mohd Razali, Sheriza; Atucha, Arnaldo Aitor Marin; Nuruddin, Ahmad Ainuddin; Abdul Hamid, Hazandy; Mohd Shafri, Helmi Zulhaidi (Taylor & Francis, 2016)
Natural forest, oil palm and rubber plantations are economically and environmentally important for Peninsular Malaysia. The present study analysed four years of moderate-resolution imaging spectroradiometer (MODIS) surface reflectance data to develop spectral indices of vegetation, water availability and moisture stress for the study area. The indices – the Normalised Difference Vegetation Index, the Normalised Difference Water Index and the Moisture Stress Index – were applied to the three different habitats to monitor drought and develop a Malaysia Southwest Monsoon (M-SWM) classification. By integrating indicators of the Southwest Monsoon, the Standard Precipitation Index, mean precipitation and temperature and spectral indices correlation analysis, M-SWM classification showed greater sensitivity to drought conditions than any of the individual indicators alone. The results also found that July is the driest month; it was the only period classified as ‘Very Dry’ based on the M-SWM.